2006
DOI: 10.1207/s15374424jccp3504_7
|View full text |Cite
|
Sign up to set email alerts
|

Family Stability as a Protective Factor Against Psychopathology for Urban Children Receiving Psychological Services

Abstract: Family stability, defined as the consistency of family activities and routines, was examined in a sample of urban families (n = 70) with children (ages 7 to 16) receiving psychological services. Parent-reported family stability was associated with lower parent-reported children's internalizing behavior problems. Child-reported family stability significantly attenuated the influence of parental depressive symptoms on parent-reported children's internalizing, externalizing, and total behavior problems, while con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 24 publications
0
32
1
6
Order By: Relevance
“…This is our family's special annual event.'' In family leisure studies, family stability is defined as consistency of family activities and routines (Ivanova & Israel, 2006). Ivanova and Israel show that sharing something within families helps family members become and stay closer together.…”
Section: Motivation Of Family Reunion Travelmentioning
confidence: 99%
“…This is our family's special annual event.'' In family leisure studies, family stability is defined as consistency of family activities and routines (Ivanova & Israel, 2006). Ivanova and Israel show that sharing something within families helps family members become and stay closer together.…”
Section: Motivation Of Family Reunion Travelmentioning
confidence: 99%
“…Higher levels of family irregularity hamper the ability of young children to develop a stable sleep onset and good quality sleep during the night (Billows et al, 2009;Buxton et al, 2015;Gregory, Eley, O'Connor, Rijsdijk, & Plomin, 2005;Spilsbury, Patel, Morris, Ehayaei, & Intille, 2017;Staples et al, 2015). Additionally, separate studies also find that family irregularity is associated with child psychopathology (Ivanova & Israel, 2006;Rijlaarsdam et al, 2016). While studies indicate that associations between sleep and child psychopathology are likely to be bidirectional (El-Sheikh & Sadeh, 2015;Gregory & Sadeh, 2016), several studies show that specific symptoms sets of developmental psychopathology, such as ADHD or autism spectrum disorder, might be underlying sleep problems and not the reverse (Owens, 2005;Richdale & Schreck, 2009;Verhoeff et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In general, children in families high in confl ict are more prone to diffi culties (Hammen et al 2004 ;Holmes et al 1999 ), while children in a positive family environment are more likely to adjust better to stress (Drotar 1997 ; Ivanova and Israel 2006 ;Varni et al 1996 ). Varni and colleagues (1996) found that in families of children with newly diagnosed with cancer, cohesion and expressiveness were associated with fewer child internalizing problems.…”
Section: Psychosocial Functioning Of Familiesmentioning
confidence: 99%